Gentle Motion, Deep Sleep and Enhanced Rehabilitation: Investigating the Impact of Rocking Movements on Sleep – A Narative Review - Damiana-Maria Vulturar; Liviu-Ștefan Moacă; Ana-Florica Chiș; Anca-Diana Maierean; Teodora-Gabriela Alexescu; Mirela -Anca Stoia; Gabriela Dogaru; Doina-Adina Todea (Balneo and PRM Research Journal, 2023)
Abstract: Sleep plays a crucial role in physical and mental well-being, being a fundamental component of the body's natural rehabilitation and recovery process. Adequate sleep not only facilitates tissue repair but also enhances cognitive function and mood. For those undergoing physical rehabilitation or recovering from injuries, prioritizing restorative sleep is indispensable, as it accelerates healing processes. Recent studies explore innovative technologies like rocking movements to enhance sleep quality. While anecdotal evidence suggests benefits, scientific literature on rocking movements remains limited. This narrative review examines the impact of rocking movements on sleep quality and memory processes. Studies suggest potential benefits, such as such as a shorter duration of N1, increased spindle density in the N2, and longer time spent in N3, indicating enhanced sleep quality. The potential relevance of these findings lies in advancing non-pharmacological treatments for individuals with insomnia or mood disorders, and they may also have implications for foraging populations dealing with reduced deep sleep and memory impairments. Further research in clinical settings is imperative to explore the impact of sleep quality on rehabilitation training, determining if the positive influences of sleep consolidation translate into substantial clinical outcomes in rehabilitative care.